Conceptual design of 5 kg/hr production of pentaerythritol tetradodecanoate (petd) - Jedidiah, Johnny (2006)
Conceptual design is becoming a common method used in the industries to estimate and design the optimum condition for their production, by concerning the time and money constraint. The objective of this study is to synthesis the process flowsheet for the optimum production of Pentaerythritol Tetradodecanoate (PETD) at 5 kg/hour. This study covers on the production cost estimation. The analytical methods of finding the properties were done using Thermogravimetry Analysis (TGA), Differential Scanning Calorimeter (DSC) and Calorimeter Bomb. To validate the conceptual design, rigorous steady state simulations are performed. Extensive simulation using ASPEN Plus software was performed and a scheme that can address the requirement is proposed. This study shows the usage of concepts to model the optimum design of reaction, separation and the utilities of PETD production. The framework which used to develop the flowsheet scheme is general enough for further investigation by extending its application to other problem.